The Impacts of The Popularity of Imported Thrift Goods to the Local Fashion Industry in Yogyakarta - Nashwa Aulia Ramadhani; Dimas Bagus Wiranatakusuma; Anggi Aprizal (Jurnal Manajemen, Akuntansi, Ekonomi, 2026)
This study aims to explore to what extent imported thrift goods affect local businesses and examine consumer preferences and market dynamics. Using a qualitative approach with a case study design, data were gathered through semi-structured interviews with a local clothing store owner and three thrift consumers. The findings reveal that its consumers highly value thrift goods for their affordability, quality, and unique appeal. Surprisingly, their popularity has not significantly affected the local store owner's business. Instead, the COVID-19 pandemic posed a more significant challenge, disrupting supply chains, reducing purchasing power, and limiting business operations for the local store. However, the thrift trend encourages local businesses to innovate through sustainable practices and culturally distinctive designs. The study concludes that the thrift market exerts limited direct pressure on local businesses; external factors like the pandemic had more profound impacts. Strategic innovation and government support are necessary to strengthen the resilience of the local fashion industry in an evolving market landscape.